The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4236/health.2016.813132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Dietary Supplement Containing Rosemary and Daylily on Biochemical Markers of Cognitive Health, Sleep Quality and Related Variables in Men and Women

Abstract: Background: We investigated the influence of a botanical agent to improve sleep quality and associated measures in men and women with self-reported difficulty sleeping. Methods: 32 individuals were randomly assigned in double blind manner to ingest a botanical agent (CLOCK®, containing Rosemary [Rosmarinus officinalis] and Daylily [Hemerocallis fulva]) or a placebo over a 6-week intervention. During weeks 1 and 2, subjects ingested one serving of the assigned condition, followed by a two-week washout. During w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In the first double blind, placebo controlled clinical trial published in 2016, CLOCK® 1g group noted increases in alertness, focus, attentiveness, feeling energetic, alertness, enthusiasm, which supports the current findings [1]. In addition, we observed an increase in feeling well rested, as well as a reduction in feeling depressed and sluggish.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the first double blind, placebo controlled clinical trial published in 2016, CLOCK® 1g group noted increases in alertness, focus, attentiveness, feeling energetic, alertness, enthusiasm, which supports the current findings [1]. In addition, we observed an increase in feeling well rested, as well as a reduction in feeling depressed and sluggish.…”
Section: Discussionsupporting
confidence: 80%
“…We have recently reported that the dietary supplement known as CLOCK®, a combination of Rosmarinus officinalis (Rosemary) and Hemerocallis fulva (Daylily), improves selected measures of subjective well-being, while resulting in favorable changes in biochemical measures of health [1]. Additional anecdotal reports using this agent have noted positive outcomes related to improved cognition and mood (e.g., increased perceived energy and enthusiasm), as well as the quality of nightly sleep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current vision of "The Plan List", Hemerocallis citrina Baroni (Xanthorrhoeaceae family), commonly known as daylily, has demonstrated multiple functions, such as antioxidant [12], sleep promoting [13], and antidepressant [14]. As recorded in the Compendium of Materia Medica, the most comprehensive and complete medicine in the history of traditional Chinese medicine, the daylily has the function of relieving gloom, and it was named 'Wang you cao' [15].…”
Section: Introductionmentioning
confidence: 99%
“…Daylilies (Hemerocallis sp L.) belong to the family Hemerocallidaceae and genus Hemerocallis [1]. It is a crop of economic importance used for natural beauty [2,3], landscaping [4,5], food nutrition [6][7][8][9], medicinal proprieties [10][11][12], and research.…”
Section: Introductionmentioning
confidence: 99%